The Influence of Creativity and Learning Innovation on Entrepreneurial Mentality and its Implications for Learning Outcomes - Bachri, Asep Sjamsul; Setiani, Ani (Fakultas Ekonomi, Universitas Negeri Semarang, 2017)
This research aims to analyze the influence of creativity and learning innovation on entrepreneurial mentality and its implications on student learning outcomes. The research was carried out in the Economic Education Program of Universitas Pasundan Bandung with 43 students as the sample of the research. The research method used descriptive quantitative method with path analysis. The results of this study are: 1) Creativity variable is in good category, with an average score of 4.06; 2) Learning innovation variable is in good category, with the score of 4,17; 3) Entrepreneurial mental variable is in good category, with an average score of 4,14; 4) Student learning outcome variables are good, with an average score of 3.94; 5) There is influence of creativity (X1) to entrepreneurial mentality (Y) with total influence of 32,8%. Learning innovation (X2) to entrepreneurial mentality (y) with total influence of 30,47%. There is an influence of creativity (X1), and learning innovation (X2), simultaneously to entrepreneurial mentality (Y) with total influence of 63,3%; 6) There is an entrepreneurial mental effect (Y) on student learning outcomes (Z) of 67.7%. It can be concluded that there are influences between creativity and learning innovation towards entrepreneurship mentality and its implication for the student learning outcomes.